2015
DOI: 10.1088/0004-6256/150/2/63
|View full text |Cite
|
Sign up to set email alerts
|

A Spectroscopic Analysis of the Galactic Globular Cluster NGC 6273 (M19)

Abstract: A combined effort utilizing spectroscopy and photometry has revealed the existence of a new globular cluster class. These "anomalous" clusters, which we refer to as "iron-complex" clusters, are differentiated from normal clusters by exhibiting large (0.10 dex) intrinsic metallicity dispersions, complex sub-giant branches, and correlated [Fe/H] and s-process enhancements. In order to further investigate this phenomenon, we have measured radial velocities and chemical abundances for red giant branch stars in th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
129
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 88 publications
(149 citation statements)
references
References 174 publications
(293 reference statements)
20
129
0
Order By: Relevance
“…In Johnson et al (2015b), we identified an intrinsic metallicity spread in NGC 6273, and noted the existence of several stars redder than the formal RGB that could belong to an even more metal-rich component. Since the previous observations were restricted to the color range 0.7 J-K S 1.0 on the upper RGB, we expanded the target selection criteria for the new observations to include stars in the color range of 0.6 J-K S 1.3.…”
Section: Magellan Spectroscopic Datamentioning
confidence: 86%
See 2 more Smart Citations
“…In Johnson et al (2015b), we identified an intrinsic metallicity spread in NGC 6273, and noted the existence of several stars redder than the formal RGB that could belong to an even more metal-rich component. Since the previous observations were restricted to the color range 0.7 J-K S 1.0 on the upper RGB, we expanded the target selection criteria for the new observations to include stars in the color range of 0.6 J-K S 1.3.…”
Section: Magellan Spectroscopic Datamentioning
confidence: 86%
“…These clusters exhibit broad metallicity distributions with discrete populations occurring near the same [Fe/H] values, and also host trace populations of metal-rich stars with peculiar chemical compositions (e.g., Pancino et al 2002;Carretta et al 2010a;Johnson & Pilachowski 2010;Marino et al 2011aMarino et al , 2015McWilliam et al 2013;Yong et al 2014;Johnson et al 2015b). In order to investigate this phenomenon further, we have obtained high-resolution spectra of >800 RGB and asymptotic giant branch (AGB) stars located near the massive bulge cluster NGC 6273.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we did not include additional broadening effects due to isotope variations for La because each star's La abundance is expected to be dominated by 139 La. The adopted atomic parameters and reference Arcturus and solar abundances can be found in Johnson et al (2015b), and a summary of the final [X/Fe] ratios for all elements measured via spectrum synthesis is provided in Tables 5-6.…”
Section: Eu Andmentioning
confidence: 99%
“…As summarized in Da Costa (2016), several lines of evidence suggest that iron-complex clusters may be the remnant cores of dwarf spheroidal galaxies that have been accreted and tidally disrupted by the Milky Way. For example, several of the most massive iron-complex clusters host metal-rich populations that have low [α/Fe], low [La/Fe], and/or lack the traditional light element abundance variations associated with globular cluster formation (Carretta et al 2010a;Johnson & Pilachowski 2010;Marino et al 2011a;Pancino et al 2011;Yong et al 2014;Johnson et al 2015;Marino et al 2015;Johnson et al 2017a), and it is possible that these stars represent the original field star populations of their parent galaxies. The two most massive iron-complex clusters ω Cen and M 54 also present strong evidence supporting accretion origins.…”
Section: Introductionmentioning
confidence: 99%